Improving Cognitive Learning Outcomes in Indonesian Language through the Group Discussion Method for Fifth-Grade Students at Baddurih State Elementary School - Nurul Khomisah; Mesfin Aberra (Journal of Action Research in Education, 2025)
This study aims to improve the cognitive learning outcomes of fifth grade students of Baddurih Elementary School in Indonesia language lessons, especially in determining main sentences and explanatory sentences through group discussion methods. By implementing this method, it is expected that students can be more actively involved in learning, so that their understanding of the material can increase and achieve the minimum completion criteria. The research design used is Classroom Action Research (CAR) which is implemented in two cycles. This research was conducted at Baddurih State Elementary School with 20 fifth grade students as subjects. Data sources were obtained through observation, interviews, and test. Data collection techniques well as observation to assess students’ activeness during learning. The collected data were analyzed descriptively to determine the comparison of learning outcomes between the pre-test and post-test. The results of the study showed an increase in students’ cognitive learning outcomes. In the pre-test, 65% of students scored below the Minimum Completion Criteria, while after the group discuccions method was implemented, 55% of students managed to achieve the Minimum Completion Criteria in the post-test. In addition, students’ active participation in the learning process also increased, as seen from their involvement in group discussion. The conclusion of this study is that the group discussion method is effective in improving students’ cognitive learning outcomes. Therefore, it is recommended that teachers continue to apply this method in learning, especially for complex materials, in order to increase student involvement and understanding.